Faktor Penyebab Artefak pada Hasil Radiograf (Soft File) Digital Radiografi di RSUD Dr. Moewardi Surakarta - Bramara, Alessandro Geo; Metaningrum, Rohmawati (Kaunia: Integration and Interconnection Islam and Science Journal, 2023)
Artifact is a structure or appearance that deviates from what should normally be seen on a radiograph (Walz-Flannigan, 2018). Artifacts can originate from various sources such as the Imaging Plate (IP), X-Ray machine, user errors, and foreign objects. All of these factors mentioned can be sources of artifacts. The aim of this research is to identify the factors and the most significant factor causing artifacts in radiographic results. This study employs a qualitative research approach utilizing a survey method. The research was conducted from June to July 2023 at RSUD Dr. Moewardi Surakarta. Data collection methods included direct observation, documentation, and interviews. The study involved 4 radiographers and 2 radiology specialist doctors as respondents. Subsequently, the collected data were processed, tabulated, and presented in the form of pie charts to draw conclusions. The research results indicate that the primary causes of artifacts in the Radiology Department at RSUD Dr. Moewardi Surakarta are: 1. Foreign objects, 2. Imaging Plate (IP), and 3. X-Ray machine. This is supported by the respective percentages of artifacts found: foreign objects 77%, Imaging Plate (IP) 19%, and X-Ray machine 4%.